Analytical model for the bond stress-slip relationship of deformed bars in normal strength concrete. (20th February 2019) - Lin, Hongwei; Zhao, Yuxi; Ozbolt, Josko; Feng, Peng; Jiang, Cheng; Eligehausen, Rolf
Highlights: A local bond stress-slip relationship model for deformed steel bar is proposed. A mathematical model for slip at the peak bond stress is proposed. A methodology for predicting the bond failure mode is suggested. The post-peak bond stress decreases nonlinearly under splitting failure mode. Abstract: The lateral confinement provided by concrete cover and stirrups has a significant influence on the bond behavior of reinforcing bars. This paper presents a systematical study on the local bond stress-slip behavior of deformed steel bars based on test results of beam-end specimens and test data reported in the literature. The bond-slip mechanism is discussed in detail and a parameter K representing the confining ability of concrete cover and stirrups is proposed. Through parameter K the bond failure mode can be predicted. With K as the governing parameter, a mathematical model for peak slip is proposed. The proposed model enables a smooth transition from splitting failure to pull-out failure. Furthermore, the nonlinear characteristics of bond stress-slip curves under splitting failure mode, which has not been well recognized in previous studies, are thoroughly discussed. By dividing the post-peak bond stress into two components, a mechanism-based mathematical model for the nonlinear descending branch of bond-slip curves is formulated. Finally, a bond-slip model for deformed steel bars is proposed, which is applicable for both splitting failure and pull-out failure modes. Comparisons with experimental results available in the literature show that the proposed model can provide good predictions for the bond-slip behavior of deformed steel bars with varying confinement levels.